2019
DOI: 10.1242/dev.174953
|View full text |Cite
|
Sign up to set email alerts
|

Revealing cellular and molecular transitions in neonatal germ cell differentiation using single cell RNA sequencing

Abstract: Neonatal germ cell development provides the foundation of spermatogenesis. However, a systematic understanding of this process is still limited. To resolve cellular and molecular heterogeneity in this process, we profiled single cell transcriptomes of undifferentiated germ cells from neonatal mouse testes and employed unbiased clustering and pseudotime ordering analysis to assign cells to distinct cell states in the developmental continuum. We defined the unique transcriptional programs underlying migratory ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 54 publications
(55 reference statements)
0
24
0
Order By: Relevance
“…In the postnatal mouse testis, prospermatogonia give rise to spermatogonia, exhausting the prospermatogonia population by postnatal day 5 (P5) ( Drumond et al., 2011 ; Kluin et al., 1982 ; Yoshida et al., 2006 ). By P6-8, distinct spermatogonial subtypes (SSC, progenitor, differentiating) can be distinguished on the basis of specific marker proteins ( Buaas et al., 2004 ; Chan et al., 2014 ; Valli et al., 2014 ), lineage tracing ( Hara et al., 2014 ; Sun et al., 2015 ), bulk ( Helsel et al., 2017 ), and single-cell (sc) ( Chen et al., 2018 ; Ernst et al., 2019 ; Green et al., 2018 ; Grive et al., 2019 ; Guo et al., 2018 ; Hermann et al., 2018 ; Jung et al., 2019 ; Law et al., 2019 ; Liao et al., 2019 ; Sohni et al., 2019 ; Velte et al., 2019 ) RNA-sequencing (RNA-seq), or transplantation analysis ( McLaren, 2003 ; Shinohara et al., 2000 ). SSCs retain regenerative capacity and divide to either self-renew or generate progenitors that lose regenerative capacity as they become primed to initiate spermatogenic differentiation giving rise to differentiating spermatogonia ( Drumond et al., 2011 ; Kluin et al., 1982 ; Yang et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the postnatal mouse testis, prospermatogonia give rise to spermatogonia, exhausting the prospermatogonia population by postnatal day 5 (P5) ( Drumond et al., 2011 ; Kluin et al., 1982 ; Yoshida et al., 2006 ). By P6-8, distinct spermatogonial subtypes (SSC, progenitor, differentiating) can be distinguished on the basis of specific marker proteins ( Buaas et al., 2004 ; Chan et al., 2014 ; Valli et al., 2014 ), lineage tracing ( Hara et al., 2014 ; Sun et al., 2015 ), bulk ( Helsel et al., 2017 ), and single-cell (sc) ( Chen et al., 2018 ; Ernst et al., 2019 ; Green et al., 2018 ; Grive et al., 2019 ; Guo et al., 2018 ; Hermann et al., 2018 ; Jung et al., 2019 ; Law et al., 2019 ; Liao et al., 2019 ; Sohni et al., 2019 ; Velte et al., 2019 ) RNA-sequencing (RNA-seq), or transplantation analysis ( McLaren, 2003 ; Shinohara et al., 2000 ). SSCs retain regenerative capacity and divide to either self-renew or generate progenitors that lose regenerative capacity as they become primed to initiate spermatogenic differentiation giving rise to differentiating spermatogonia ( Drumond et al., 2011 ; Kluin et al., 1982 ; Yang et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many scRNAseq experiments have been conducted on murine testicular cells [8,9,10,11,12,13,14,15,16,17,18,19,97]. Green and Wang’s works, both of which were published in 2018, mapped the gene expression dynamics of adult germ cell maturation in mice and humans, respectively [9,19].…”
Section: Scrnaseq: a New Way To Explore Spermatogenesismentioning
confidence: 99%
“…In addition to the many scRNAseq studies on spermatogenesis in neonatal, prepubertal, and adult mice [7,8,9,10,11,12,13,14,15,16,17,18], which provided unbiased classifications of spermatogonial stem cell (SSC) pools and differentiation states, an atlas of human spermatogenesis at three different developmental stages (neonatal, prepubertal, and adult) has also been described recently thanks to this method [12,19,20,21,22,23]. The atlas reveals the striking heterogeneity among testicular somatic and germinal cell populations and assesses the identity of human SSC (hSSC) and spermatogonial progenitors.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cxcr4 and Foxc2 promote migration and invasiveness through EMT in different types of cancer [14][15][16][17][18] . CD87 (urokinase-type plasminogen activator (uPA) receptor/uPAR), a marker for neonatal undifferentiated spermatogonia, can be regulated by TGFβ and participates in tumor invasion and metastasis [19,20] . Recent whole transcriptome analysis also confirmed that THY1+ subpopulations of neonatal germ cells were mesenchymal-like due to higher levels of EMT genes ( Vim , Zeb2 ), while the ID4+ population (SSC-enriched) expressed lower levels of EMT genes [21] .…”
Section: Introductionmentioning
confidence: 99%
“…To address this knowledge gap, we searched for potential candidates from our previous single cell RNA-seq study on neonatal undifferentiated germ cells. We found Euchromatic histone-lysine N-methyltransferase 2 (EHMT2), also known as G9a, particularly interesting as it is one of the transcriptional regulators upregulated in differentiation-primed spermatogonia ( Gfra1 −/ Kit − cells) [19] . Moreover, neonatal differentiation-primed germ cells expressed higher levels of mesenchymal markers (e.g.…”
Section: Introductionmentioning
confidence: 99%